Degrees of freedom as a breeding ground for biases-A threat to forensic practice - Oeberst, Aileen; Oberlader, Verena (Law and human behavior, 2024)
Researcher-based degrees of freedom have been shown to contribute to low replication rates in science. That is, researchers' options within the process of designing and conducting empirical tests may increase the probability of false positive findings. The aim of this study was to transfer the concept of degrees of freedom to the practice of forensic-psychological assessment as it may likewise pose a severe threat to the reliability and validity of forensic assessments. Using an example from statement validity assessment, we identified degrees of freedom, calculated the different possible workflows that forensic experts can take, and elaborated on their consequences for the reliability and validity of their assessments. Importantly, we elaborated on why degrees of freedom likely not only increase noise in the results but also foster the occurrence of systematic biases in forensic practice. Degrees of freedom in forensic-psychological assessments exist and lead to an enormous number of different possible workflows. As this threatens the interrater reliability and validity of forensic assessments and may lead to biases, we call for research on this issue and put forward recommendations for forensic practice. (PsycInfo Database Record (c) 2025 APA, all rights reserved).